Efik Nominal Tonal Alternations As Phrasal Morphology - Glewwe, Eleanor (My University, 2019)
Certain Efik nominal constructions exhibit fixed tonal melodies that overwrite nouns’ underlying tones. Previous analyses of these alternations (Welmers 1973; Kim 1974; Cook 1985) are purely phonological. Working in a constraint-based framework, I propose that the tonal alternations are actually phrasal morphology (McPherson 2014). The tonal melodies are overlays encoded in lexicalized constructional schemas that relate idiosyncratic phrasal phonology with specific syntactic constructions. The constructional schemas are enforced by constraints. The Efik case extends the observed range of phrasal morphology by demonstrating that constructional schema constraints and phonological constraints can interact to determine a construction’s surface tones
Keywords: phrasal morphology; tonal alternations; Efik